Prosedur kesehatan dan keselamatan kerja dengan angka kejadian covid-19 - Marisca Jenice Sanaky (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Coronavirus Disease-19 (COVID-19) is a disease that causes respiratory distress and pneumonia. This disease is caused by infection with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2). WHO encourages all countries to develop COVID-19 vaccines with the aim of forming herd immunity. This study aims to determine the relationship between occupational health and safety procedures and the incidence of COVID-19 in employees at Sandi Karsa Hospital Makassar. The type of research used is analytical with a cross-sectional study method. The number of samples of 200 people was obtained by total sampling technique. Data collection by filling out questionnaires and data tested with the Pearson test. The results of the correlation analysis test between occupational health and safety procedures and the incidence of COVID-19 in employees at Sandi Karsa Hospital Makassar obtained a value of p = 0.000 (p < 0.005). Therefore, the conclusion of this study is that there is a significant relationship between occupational health and safety procedures and the incidence of COVID-19 in employees at Sandi Karsa Hospital Makassar.